Tradisi Baca Tulis Dalam Islam Kajian Terhadap Teks AlQur’an Surat Al ‘Alaq Ayat 1 - 5 - Mustolehudin Mustolehudin (Analisa: Journal of Social Science and Religion, 2011)
The first verse revealed from Allah to Prophet Muhammad was an instruction  toread and to write. Reading is an urgent and important thing for people. Knowledge and information can be acquired by reading.  Instruction to read can be seen in many verses of Qur’an, it is stated twelve times; three times in the form of fi’il amar, two times in the form of fi’il mudari’ (verb; present tense), four times in the form of fi’il mādi (verb; past tense). Reading in the broad meaning is a person who has capability to examine, to study, to know the characteristic of thing and to collect knowledge andinformation. Reading materials which are read by people are all the thingswhich can be gotten whether in a holy text (holy book/kitab), written verses or unwritten verses. Capability of reading and writing can be achieved by education whether formal education or non formal education.